One method for the investigation of the fundamental solution of the Cauchy problem for parabolic systems - Litovchenko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
A recursive method for the investigation of the fundamental solution of the Cauchy problem for parabolic Shilov systemswith time-dependent coefficients is proposed. It is based on the general formula for the solution of linear inhomogeneoussystems of differential equations of the first order and does not require the use of the genus of the analyzed system.